Pyridazine Based Scaffolds as Privileged Structures in anti-Cancer Therapy - Jaballah, Maiy Youssef; Serya, Rabah Taha; Abouzid, Khaled (Drug Research, 2017)
Pyridazines, their oxo derivatives; pyridazinone as well as fused bi- or tricyclic pyridazine containing scaffolds are key structural features of many biologically active compounds with diverse pharmacological applications, including cancer therapy. Since protein kinases play prominent role in tumor biology, the inhibition of its signaling pathway is considered an effective therapeutic option for the treatment of cancer.Based on the various advantages of pyridazines in drug design including modulation of the physico-chemical properties, improving ADME and toxicity profile as well as easy and diverse synthetic methods of access, makes them an invaluable tool for designing compounds as future drugs for targeted cancer treatment.In this review, we have compiled and discussed the anticancer potential of pyridazine based scaffold, with special focus on those targeting protein kinase inhibition.
Keywords: pyridazines; anti-cancer; kinases; anti-proliferative